Subjective memory impairment in glioma patients with curative radiotherapy. (June 2022) - Donix, Markus; Seidlitz, Annekatrin; Buthut, Maria; Löck, Steffen; Meissner, Gisa; Matthes, Claudia; Troost, Esther G.C.; Baumann, Michael; Raschke, Felix; Linn, Jennifer; Krause, Mechthild
Highlights: Radiotherapy of brain tumors may cause dose-dependent side-effects. HipPro Pilot study using structural MRI and comprehensive neurocognitive evaluation. Hippocampal thickness or objective memory performance did not change. Subjective memory impairment was associated with symptoms of depression. Future studies of memory impairment should assess depressive symptoms. Abstract: Background: Radiotherapy in patients with primary brain tumors may affect hippocampal structure and cause dyscognitive side-effects. Patients and methods: Using structural MRI and comprehensive neurocognitive evaluation, we investigated associations between hippocampal structure and memory deficits in 15 patients with WHO grade 3 and grade 4 gliomas receiving standard radio(chemo)therapy. Results: We did not find changes in hippocampal thickness or cognitive abilities three months after completing radiotherapy. However, subjective memory impairment was associated with symptoms of depression, but not with objective memory performance, cortical thickness of the hippocampus or radiation dose. Conclusions: Irrespective of whether there is a bidirectional relationship between affective changes and subjective cognitive dysfunction in these patients, depressive symptoms remain a target for intervention to improve their quality of life. The results of our pilot study highlight that future assessment of side effects of radiotherapy concerning memory should include assessments of depressive symptoms.